Kaizen Culture and Employee Performance in the Post-COVID-19 Era: Does Servant Leadership Mediate in the Model ? - Muhamad Ekhsan; Ryani Dhyan Parashakti; Yoga Religia; Ivhan Moulana (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Performance is used to measure the results that have been achieved related to the company's activities. Employee performance is seen through the achievement of tasks that are in line with the work program that has been prepared. Kaizen culture and leadership style from environmental factors are two factors that influence the increase in employee performance from organizational culture factors. This study aims to examine the direct and indirect relationship between the variables of Kaizen culture, servant leadership, and employee performance with the object of research, namely one of the automotive manufacturing companies. The research was conducted using quantitative methods. The population used is all employees of an automotive manufacturing company, with a total sample size of 62 respondents. The sampling technique used is the probability sampling technique with the saturated sample method. Data collection is done through Google Forms when filling out online surveys. analysis of the data in this study using the SmartPLS version 3.0 software program. The results of the study state that kaizen culture has a positive and significant effect on employee performance, kaizen culture has a positive and significant effect on servant leadership, servant leadership has a positive and significant effect on employee performance, and kaizen culture has a positive and significant effect on employee performance mediated by servant leadership.